High‐resolution melting analysis for bird sexing: a successful approach to molecular sex identification using different biological samples. (25th February 2013) - Morinha, Francisco; Travassos, Paulo; Seixas, Fernanda; Santos, Nuno; Sargo, Roberto; Sousa, Luís; Magalhães, Paula; Cabral, João A.; Bastos, Estela
Abstract High‐resolution melting (HRM) analysis is a very attractive and flexible advanced post‐PCR method with high sensitivity/specificity for simple, fast and cost‐effective genotyping based on the detection of specific melting profiles of PCR products. Next generation real‐time PCR systems, along with improved saturating DNA‐binding dyes, enable the direct acquisition of HRM data after quantitative PCR. Melting behaviour is particularly influenced by the length, nucleotide sequence and GC content of the amplicons. This method is expanding rapidly in several research areas such as human genetics, reproductive biology, microbiology and ecology/conservation of wild populations. Here we have developed a successful HRM protocol for avian sex identification based on the amplification of sex‐specific CHD1 fragments. The melting curve patterns allowed efficient sexual differentiation of 111 samples analysed (plucked feathers, muscle tissues, blood and oral cavity epithelial cells) of 14 bird species. In addition, we sequenced the amplified regions of the CHD1 gene and demonstrated the usefulness of this strategy for the genotype discrimination of various amplicons (CHD1Z and CHD1W), which have small size differences, ranging from 2 bp to 44 bp. The established methodology clearly revealed the advantages (e.g. closed‐tube system, high sensitivity and rapidity) of a simple HRM assay for accurate sex differentiation of the species under study. The requirements, strengths and limitations of the method are addressed to provide a simple guide for its application in the field of molecular sexing of birds. The high sensitivity and resolution relative to previous real‐time PCR methods makes HRM analysis an excellent approach for improving advanced molecular methods for bird sexing.